Current issues against smuggling in Ukraine - Шустрова, Ксенія Володимирівна; Шустрова, К. В.; Шустрова, Ксения Владимировна; Shustrova, Kseniia V.; Богатирьова, Марина Олександрівна; Богатирьова, М. О.; Богатырёва, Марина Александровна; Bohatyrova, Maryna O. (Одеса : Видавничий дім «Гельветика», 2021)
It is determined that in Ukraine there is an administrative and criminal liability for smuggling. Therefore, depending on the legal responsibility that is provided during the implementation of smuggling, smuggling is divided into: 1) smuggling, for which criminal liability is provided; 2) smuggling, for which administrative liability is provided. In addition, it is concluded that based on the definition of smuggling and directly the objects of smuggling, the following types of smuggling can be distinguished: 1) smuggling of historical and cultural values; 2) smuggling of explosives, radioactive materials, weapons or ammunition (except for smooth-bore hunting weapons or ammunition), parts of firearms; 3) smuggling of timber or lumber of valuable and rare species of trees, unprocessed timber, as well as other timber prohibited for export outside the customs territory of Ukraine; 4) smuggling of narcotic drugs, psychotropic substances, their analogues or precursors or falsified drugs; 5) smuggling of special technical means of covert receipt of information; 6) others. It has been established that in addition to the listed items of smuggling, criminalization requires the smuggling of valuable and rare species of animals and plants and (or) endangered animals and plants, microbiological or other biological agents or toxins, transplant organs or human tissues, etc., as well as some types of smuggling in the field of transportation of goods and materials. Therefore, it is proposed to supplement the definition of smuggling by moving across the customs border of Ukraine outside customs control or with concealment from customs control of alcoholic beverages, tobacco products committed in significant amounts. And also Art. 201 of the Criminal Code to supplement the provisions on smuggling of alcoholic beverages, tobacco products committed in large amounts and in especially large amounts, as well as committed by prior conspiracy by a group of persons or a person previously convicted of a crime under this article or an official using official position. It is determined that in accordance with the most common classification of state bodies by the criterion of the breadth of competence, there are state bodies of general and special competence. If we follow this classification, the general bodies of counteraction to smuggling are state bodies of general competence, which are the Cabinet of Ministers of Ukraine, the President of Ukraine, the Verkhovna Rada of Ukraine. The bodies of special competence are the security forces, judicial and law enforcement agencies.

Визначено, що в Україні передбачена адміністративна та кримінальна відповідальність за контрабанду. Тому, в залежності від юридичної відповідальності, яка настає при здійсненні контрабанди, контрабанда поділяється на: 1) контрабанду, за яку передбачена кримінальна відповідальність; 2) контрабанду, за яку передбачена адміністративна відповідальність. Крім того, зроблено висновок, що виходячи з визначення контрабанди та безпосередньо предметів контрабанди можна відокремити такі види контрабанди: 1) контрабанда історичних та культурних цінностей; 2) контрабанда вибухових речовин, радіоактивних матеріалів, зброї або боєприпасів (крім гладкоствольної мисливської зброї або боєприпасів), частин вогнепальної нарізної зброї; 3) контрабанда лісоматеріалів або пиломатеріалів цінних і рідкісних порід дерев, лісоматеріалів або пиломатеріалів необроблених, а також інших лісоматеріалів, заборонених до вивозу за межі митної території України; 4) контрабанда наркотичних засобів, психотропних речовин, їх аналогів або прекурсорів або фальсифікованих лікарських засобів; 5) контрабанда спеціальних технічних засобів негласного отримання інформації; 6) інші. Встановлено, що на додаток до перелічених предметів контрабанди, криміналізація вимагає контрабанди цінних і рідкісних видів тварин і рослин та (або) тварин і рослин, що знаходяться під загрозою зникнення, мікробіологічних чи інших біологічних агентів або токсинів, трансплатанційних органів або тканин людини, тощо, а також деякі види контрабанди у сфері перевезення товарно-матеріальних цінностей. Тому запропоновано доповнити визначення контрабанди переміщенням через митний кордон України поза митним контролем або з приховуванням від митного контролю алкогольних напоїв, тютюнових виробів, вчинене у значних обсягах. А також ст. 201 КК, щоб доповнити пунктами щодо контрабанди алкогольних напоїв, тютюнових виробів, вчинене у великих та особливо великих розмірах, а також вчинені за попередньою змовою групою осіб або особою, раніше судимою за злочин, передбачений цією статтею, або службовою особою з використанням службового становища. Визначено, що відповідно до найбільш розповсюдженої класифікації державних органів за критерієм ширини компетенції виділяються органи держави загальної та спеціальної компетенції. Якщо дотримуватись такої класифікації, загальними органами протидії контрабанді є державні органи загальної компетенції, якими виступають Кабінет Міністрів України, Президент України, Верховна Рада України. Органами спеціальної ​​компетенції є Служба безпеки України, Міністерство внутрішніх справ, Державна прикордонна служба України, Державна фіскальна служба України, прокуратура, інші правоохоронні органи та суд.
Shustrova K. V. Current issues against smuggling in Ukraine / K. V. Shustrova, M. O. Bohatyrova // Наукові праці Національного університету «Одеська юридична академія». Т. 28 / голов. ред. Ю. В. Цуркан-Сайфуліна ; МОН України, НУ «ОЮА». – Одеса : Видавничий дім «Гельветика», 2021. – C. 145-151.
Keywords: smuggling; law enforcement agencies; security forces; drugs; precursors; goods; types of smuggling; контрабанда; правоохоронні органи; сили безпеки; наркотичні засоби; прекурсори; товари; види контрабанди; Research Subject Categories::LAW/JURISPRUDENCE